Optimal Suppression of Photocatalytic Activity of Hybrid TiO2 Particles in Epoxy Thin Film by Using Taguchi Method - Muniandy, Sunderishwary S.; Soon, Tan Sek; Pung, Swee Yong; Ramakrishnan, Sivakumar (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
In this study, two different Al2O3-TiO2 and SiO2-TiO2 hybrid TiO2 particles were synthesised by using silica (SiO2) and alumina (Al2O3) to suppress the photocatalysis of TiO2. Key variables such as the concentration of the hybridization material (C), heating temperature (Th), and calcinating temperature (Tc) were selected with performance measured by photodegradation rate. The Taguchi L9 orthogonal array, a systematic approach used in the design of experiments (DOE), confirmed A333 (Al2O3-TiO2) achieved 99% photodegradation suppression with photodegradation rate reduced significantly from 0.01305 min−1 to 0.00009 min−1 and improved yellowing resistance by 63%, while S323 (SiO2-TiO2) achieved 75% suppression with photocatalysis activity decreased from 0.01305 min−1 to 0.0033 min−1 and 42% improved resistance. X-ray Diffraction (XRD) analysis showed A333 had a higher rutile phase (40.1% vs. 10.2% for S323), and Fourier Transform Infra Red (FTIR) and Field Emission Scanning Electron Microscopy (FESEM) analyses revealed A333's rougher surface and lower surface area compared to S323 and pure TiO2. Overall, A333 effectively suppressed photocatalysis and improved yellowing resistance of epoxy thin film. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).